Microbial diversity of Pekan peat swamp forest soil and their functional potential through cultivation and metagenomic approach - Mohd Omar, Suhaila (2018)
Tropical peat swamp serves as the global pool of terrestrial organic carbon which mostly in the form of lignin, the major constituent of plant materials. The South-East Pahang Peat Swamp Forest (SEPPSF) that lies in Pekan district is believed to be mainland Asia’s largest and least disturbed peat swamp forest. The ecology and the biodiversity of this environment are poorly understood. Even though several systematic researches have been conducted on flora and fauna in this environment, data on microbial diversity is scarce despite of its importance towards terrestrial ecosystem functioning. Due to the highly acidic environment, low concentrations of nutrients and anoxic condition, microbial species in the peat swamp environment are slow-growing, difficult to isolate and manipulate in the laboratory.